Beyond Bekenstein’s Theory - Kraiselburd, Lucila (2010)
There are several very different motivations for studying the variation of fundamental constants. They may provide a connection between cosmology and particle physics due to the coincidence of large dimensionless numbers arising from the combination of different physical constants. Bekenstein’s variable charge model is very attractive because it is based on very general assumptions: covariance, gauge invariance, causality and time-reversal invariance of electromagnetism. The generality of its assumptions guarantee the applicability of the scheme to other gauge interactions such as the strong forces. Besides, it introduces a useful simplifying assumption; namely, that the gravitational sector is unaffected by the scalar field introduced to vary the coupling constant. That is why it is interesting to explore first this simplified model, before a similar exploration of more general theories.